Chemo‐taxonomic and biological potential of highly therapeutic plant Pedicularis groenlandica Retz. using multiple microscopic techniques. Issue 12 (2nd June 2021) - Hameed, Ayesha; Zafar, Muhammad; Ahmad, Mushtaq; Sultana, Shazia; Bahadur, Saraj; Anjum, Farida; Shuaib, Muhammad; Taj, Sehrish; Irm, Misbah; Altaf, Muhammad Ahsan
Abstract: Pedicularis groenlandica is one of the most important medicinal plant of Deosai Plateau (Gilgit‐Baltistan) Pakistan. The present study was aim to evaluate the micromorphological features, phytochemical screening and pharmacological potential of P. groenlandica by using multiple microscopic techniques. Six different solvents were used to prepare P. groenlandica extracts. Phytochemical and antioxidant activities were determined calorimetrically. To investigate antidiabetic, α‐amylase inhibition assay was performed. Cytotoxicity was tested using brine shrimp assay. Anti‐leishmanial via MTT assay. Disc‐diffusion assay was used for protein kinase inhibitory, antibacterial and antifungal activities. Palyno‐anatomical study showed significant variation for the authentication and correct identification of this highly therapeutic plant by using light and scanning electron microscopic techniques. All extracts were found rich in phytochemicals, significant amount of phenolic and flavonoid contents were found in methanol extract (PGM) 95.78 mg GAE/g and 66.90 mg QE/g. Highest DPPH scavenging potential with IC50 88.65 μg/mL, total antioxidant capacity (60.33 mg AAE/g sample) and total reducing power (83.97 mg AAE/g) were found for PGM. Disc‐diffusion method showed significant antibacterial and antifungal activities. Noticeable growth inhibition in L. tropica was displayed by n‐hexane extract (IC50 112 μg/mL). Brine shrimp with highest LD50 (67.65 μg/mL) in ethyl‐acetate extract. Ethanol extract gives persuasive protein kinase inhibition (26 mm) against Streptomyces 85‐E hyphae. Highest alpha‐amylase inhibition (74.10%) was found in n‐hexane extract. In conclusion, our findings scientifically support the ethno‐medicinal and biological potential of P. groenlandica . In future, the plant needs to be explored for further identification and isolation of bioactive compounds to develop new drugs to treat several aliments. Abstract : The micromorphological features, phytochemical screening and pharmacological potential of P. groenlandica were evaluated by using multiple microscopic techniques. Phytochemical and antioxidant activities were determined calorimetrically and for antidiabetic, α‐amylase inhibition assay was performed. Cytotoxicity was tested using brine shrimp assay, anti‐leishmanial via MTT assay. Disc‐diffusion assay was used for protein kinase inhibitory, antibacterial and antifungal activities. Palyno‐anatomical study showed significant variation for the authentication and correct identification of this highly therapeutic plant by using light and scanning electron microscopic techniques. Our findings scientifically support the ethnomedicinal and biological potential of P. groenlandica .